(untitled) (Journal of Computational Mathematics, 1999)
To solve the potential inversion problem of the coupled system for one-way wave equations, the absorbing boundary conditions in the lateral direction are derived. The difference schemes are constructed and a layer stripping method is proposed. Some numerical experiments are presented.